2016
DOI: 10.5603/kp.a2016.0002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect of vitamin D deficiency in patients with acute myocardial infarction

Abstract: A b s t r a c tBackground: Vitamin D is a major regulator of mineral bone metabolism. The lower vitamin D levels in patients with acute myocardial infarction (AMI) and the seasonal variation of vitamin D levels are proposed. Aim:The evaluation of the seasonal relationship of 25(OH)D levels in patients with AMI and analysis of confounding factors (gender or diabetes mellitus) affecting the levels of vitamin D in AMI patients.Methods: Fifty-nine consecutive patients with mean age 58 ± 9.4 years were admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Discrepancies between these values were most probably caused by different time of blood sampling, considering the half-life of 25(OH)D defined was twenty-five days, and lack of skin synthesis in winter could influence the findings. This so-called “seasonal effect” being coherent with our results was also reported by Tokarz et al in the acute myocardial infarction group of patients [ 36 ]. It is worth to mention that 25(OH)D concentration during winter is based upon food intake and previous liver storage.…”
Section: Discussionsupporting
confidence: 93%
“…Discrepancies between these values were most probably caused by different time of blood sampling, considering the half-life of 25(OH)D defined was twenty-five days, and lack of skin synthesis in winter could influence the findings. This so-called “seasonal effect” being coherent with our results was also reported by Tokarz et al in the acute myocardial infarction group of patients [ 36 ]. It is worth to mention that 25(OH)D concentration during winter is based upon food intake and previous liver storage.…”
Section: Discussionsupporting
confidence: 93%
“…Elevated MP levels, such as TF-positive MPs, have been shown to be one of the procoagulant determinants in patients with type 2 diabetes mellitus [82]. Also, it was demonstrated that EVs participate in the transport of cytokines and angiogenic factors in diabetic patients with ocular complications [83]. Moreover, a recent study showed that distribution of pro-and anti-angiogenic miRNAs in patients with type 2 diabetes is in close touch with the upregulation or downregulation of miRNAs in the plasma fraction enriched in ectosomes (MVs or MPs) [84].…”
Section: Extracellular Vesicles As Clinical Biomarkers Therapeutic Tmentioning
confidence: 99%
“…Thus, vitamin D deficiency may play a role in MI. It is further supported by a high prevalence of vitamin D deficiency in acute MI patients [5455]. However, studies have reported no association between vitamin D levels, inflammatory markers, and patients with ACS [5657].…”
Section: Cardiac Diseasesmentioning
confidence: 99%